(3CSGSjGJ aj GdEOGQI GdeGdjI (B/s - (3GdfYjej, YOfGf JGjgs; (3GdNQTg, jGSjf cGSHs ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2007)
(3JYO GdGOGQI GdeGdjI GMOi GdhXGFa GdGSGSjI ef hXGFa GdefTBJ, chfgG JJYGed eY GdehQO GdeGdj GdPj jTcd GMO GdOYGeGJ dHbGA GdefTBJ hGSJeQGQGgG, hbO GROGOJ GgejI GdGOGjQI GdeGdjI aj GdYbhO GdGNjQI fJjLI dJaGYd GdYOjO ef GdYhGed ef HjfgG GQJaGY MOI GdefGaSI Hjf GdeTQhYGJ GdGbJUGOjI GdeNJdaI(B. (3JRGjO GdOhQ GdPj GNPJ JdYHg GdGShGb GdeGdjI ef chfgG GUHMJ GdeQBI GdJj jecf ef NdGdgG GdJYQa Ydi GdeQGcR GdeGdjI hGdJTZjdjI ddefTBJ, GdJWhQ GdcHjQ hGdeJSGQY aj JcfhdhLjG GdeYdheGJ hGdGJUGdGJ hGfJTGQ GSJNOGeGJgG(B. (3cd eG JbOe GOi Gdi RjGOI GdOhQ GdPj JdYHg GdGOGQI GdeGdjI aj JYXje bjeI GdefTCI aj Shb GdGhQGb GdeGdjI ef NdGd GdGgJeGe Hcd GdYhGed GdJj JeJdc GdJCKjQ aj Jdc GdbjeI(B. (3hbO LGA GdcJGH GdMGdj djHdj MGLI GdeNJUjf aj eLGdGJ GdGOGQI GdeGdjI GdeNJdaI, ceG Gfg jdHj MGLI GdegJejf aj OQGSI gPG GdehVhY GdMjhj chfg jJVef GdWQhMGJ GdfXQjI ddehVhYGJ GdeGdjI Gdi LGfH GdYOjO ef GdGeKdI hGdJWHjbGJ GdJj JgOa Gdi GjUGd acQI cd ehVhY ef GdehVhYGJ GdeWQhMI ajg(B. (3hJVef GdcJGH SHYI aUhd JJfGhd GdLhGfH GdGSGSjI ddGOGQI GdeGdjI hJWHjbGJgG hceG jdj(B: (3GdaUd GdGhd(B: (3QcR Ydi GdJYQja HGdGOGQI GdeGdjI chXjaI hceLGd ef eLGdGJ GdeYQaI ef NdGd GdJYQja HeLGdGJ GdeGdjI, GgOGa GdGOGQI GdeGdjI, heSDhdjGJgG hehbYgG aj Gdgjcd GdJfXjej ddefTGI(B. (3ceG Je GjVGM GdYdGbI Hjf cd ef GdQHMjI hHjf GdSjhdI(B. (3GdaUd GdKGfj(B: (3JfGhd gPG GdaUd YOO ef GdSjGSGJ GdeGdjI PGJ GdYdGbI HgOa JYXje bjeI GdefTCI hGdJWHjbGJ GdeQJHWI HgPg GdSjGSGJ(B. (3hef Hf Jdc GdSjGSGJ(B: (3SjGSI GSJFLGQ GdGUhd GdKGHJI cHOjd ef HOGFd GdJehjd Whjd GdGLd, SjGSI GdGgJdGc (B((3GdGfOKGQ(B) (3GdJj JgJe HMSGH GbSGW GgJdGc GdGUhd GdKGHJI hJCKjQ Pdc aj GdVQjHI GdeOahYI ef bHd GdefTCI, hCNjQG GdSjGSI GdHjYjI Gh eG jWdb YdjgG GdSjGSI GdGFJeGfjI(B. (3GdaUd GdKGdK(B: (3LGA gPG GdaUd djdbaj GdVhA Ydi GMO egGe GdGOGQI GdeGdjI GdG hgj hXjaI GdJNWjW GdeGdj hPdc ef NdGd GHQGR GgejI GdJNWjW HGWGQI GdYGe hGdJNWjW GdeGdj HTcd NGU hGdJYQja HHYV GdGOhGJ GdeSJNOeI aj YedjI GdJNWjW GdeGdj(B. (3GdaUd GdQGHY(B: (3Gdgjcd GdeGdj hechfGJg, GdJj JTcd eUGOQ GdJehjd GdeJGMI GeGe GdefTCI gh fbWI GgJeGe gPG GdaUd, MjK Je GdJQcjR Ydi eUGOQ GdJehjd bUjQ GdGLd, eUGOQ GdJehjd GdebJQV eJhSW hWhjd GdGLd, hCNjQG eUGOQ GdJehjd GdeeJdc eJhSW hWhjd GdGLd(B. (3GdaUd GdNGeS(B: (3NUU gPg GdaUd defGbTI HYV GdYhGed GdeDKQI aj UjGZI Gdgjcd GdeGdj defTBJ GdGYeGd, Mj Je GdJQcjR Ydi Jdc GdYhGed GdJj JTcd eMOOGJ GSjGSjI YfO GJNGP Cj bQGQ ddMUhd Ydi GdGehGd ef eUGOQ GdJehjd GdeNJdaI(B. (3GdaUd GdSGOS(B: (3gjcd GdGSJKeGQ Gh eG jWdb Ydjg aj eQGLY GdGOGQI GdeGdjI (B"(3bQGQ GdGSJKeGQ(B"(3, GdPj jQJHW HJTcjdI GdGUhd GdJj Ydi GdefTCI GdGSJKeGQ ajgG ef GLd JMbjb GdGgOGa GdJj hLOJ GdefTCI ef GLd JMbjbgG(B. (3hgPG GdehVhY cGf LhgQ JQcjR GdaUd GdePchQ(B. (3daUd GdSGHY, hbO cGf ddQjGVjGJ GdeGdjI, GdJj JJVef GdYOjO ef GOhGJ GdMSGH GdeJYdbI HGdehQO GdeGdj, ecGfG aj gPG GdcJGH, MjK Je GdJQcjR Ydi GSJYQGV JYQja GdaGFOI hGfhGYgG hYdGbI gPg GdaGFOI HGdbjeI GdRefjI ddfbhO(B.s
(3HjHdjhZQGajG(B: (3U(B.349s
Keywords: (3GdEOGQI GdeGdjIs; (3GdJNWjW GdEbJUGOjs; (3GdeGdjI GdYGeIs